CT-guided biopsy in suspected spondylodiscitis: the association of paravertebral inflammation with microbial pathogen detection - Spira, Daniel; Germann, Thomas; Lehner, Burkhard; Hemmer, Stefan; Akbar, Michael; Jesser, Jessica; Weber, Marc-André; Rehnitz, Christoph (PLOS ONE, 2016)
Objectives To search for imaging characteristics distinguishing patients with successful from those with futile microbiological pathogen detection by CT-guided biopsy in suspected spondylodiscitis. Methods 34 consecutive patients with suspected spondylodiscitis underwent CT-guided biopsy for pathogen detection. MR-images were assessed for inflammatory infiltration of disks, adjacent vertebrae, epidural and paravertebral space. CT-images were reviewed for arrosion of adjacent end plates and reduced disk height. Biopsy samples were sent for microbiological examination in 34/34 patients, and for additional histological analysis in 28/34 patients. Results Paravertebral infiltration was present in all 10/10 patients with positive microbiology and occurred in only 12/24 patients with negative microbiology, resulting in a sensitivity of 100% and a specificity of 50% for pathogen detection. Despite its limited sensitivities, epidural infiltration and paravertebral abscesses showed considerably higher specificities of 83.3% and 90.9%, respectively. Paravertebral infiltration was more extensive in patients with positive as compared to negative microbiology (p = 0.002). Even though sensitivities for pathogen detection were also high in case of vertebral and disk infiltration, or end plate arrosion, specificities remained below 10%. Conclusions Inflammatory infiltration of the paravertebral space indicated successful pathogen detection by CT-guided biopsy. Specificity was increased by the additional occurrence of epidural infiltration or paravertebral abscesses.
Gesehen am 12.05.2020